2017
DOI: 10.1159/000452656
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Follow-Up Strategies for Gastrointestinal Stromal Tumor Patients Based on the Analysis of Recurrent Interval and Patterns

Abstract: Background/Aims: Previous studies have proposed risk classifications for patients with gastrointestinal stromal tumor (GIST) after resection and have contributed to the prediction of its prognosis. However, optimal postoperative surveillance has not yet been established. Methods: We retrospectively analyzed data from 115 GIST patients who experienced recurrence after complete resection. The relationships between clinicopathological characteristics and the first recurrence sites, or time to recurrence (TTR), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In one study conducted by Italian researchers ( 6 ), reviews of 42 patients who underwent treatment for GIST recurrence in their institution indicated that the incidence of patients with late recurrence of five years or later was 14%. One Japanese study of 115 patients who developed recurrence after surgery ( 22 ) revealed that the incidence of late recurrence was 12.2%. These findings suggest that five-year follow-up is insufficient to determine the oncological outcomes of GIST patients, and longer follow-up is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study conducted by Italian researchers ( 6 ), reviews of 42 patients who underwent treatment for GIST recurrence in their institution indicated that the incidence of patients with late recurrence of five years or later was 14%. One Japanese study of 115 patients who developed recurrence after surgery ( 22 ) revealed that the incidence of late recurrence was 12.2%. These findings suggest that five-year follow-up is insufficient to determine the oncological outcomes of GIST patients, and longer follow-up is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no known clinicopathological feature that can enable the effective selection of patients requiring long follow-up of more than five years. Although the above-mentioned Japanese study ( 22 ) revealed that small and low-risk GISTs were frequently found in cases of late GIST recurrence, those features are substantially useless for patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Risk stratification of each primary GIST was defined on the basis of histopathological reports which were graded using the modified National Institutes of Health criteria, including factors such as tumor diameter, site, mitotic index, and presence of rupture at surgery (21). Patients with moderate-to-high risk GISTs were categorized into the high-risk recurrence group (H-group, higher recurrence rate within 5 years) and patients with very-low-and-low risk GISTs were assigned to a low-risk recurrence group (L-group, lower recurrence rate within 5 years) (22,23).…”
Section: Reference Standardsmentioning
confidence: 99%